Pengaruh Kedisiplinan, Keselamatan dan Kesehatan Kerja Terhadap Produktivitas KerjaKaryawan Pada PT JMS Batam - Otinia Zega; Nora Pitri Nainggolan (eCo-Buss, 2024)
The purpose of this study is to anayze the influence of work discipline, safety and heath partialy and simultaneously on the work of employees of PT. JMS Batam. This study uses a quantitative approach. The population in this study is al employees in Burret PA in 2022 at PT. JMS Batam has 160 employees. Determining the number of samples using saturated samples from the entire population and the sampling technique using incidenta sampling so that the number of questionnaires returned was 120 questionnaires, thus the sample used in this study totaed 120 samples. This study shows conclusively that: (1) Work discipline partialy has a significant effect on employee work productivity, with a t count of 8.216 > 1.980 from t table and obtains a significance vaue of 0.00 <0.05. (2) Occupationa safety and heath partialy have a significant effect on employee work productivity, with a t count of 5.995 > 1.980 from t table and obtain a significance vaue of 0.00 <0.05. (3) Work discipline, occupationa safety and heath simultaneously have a significant effect on employee work productivity, with a caculated f vaue of 103.291 > 3.09 from ftable and obtain a significance vaue of 0.00 <0.05. (4) The magnitude of the influence of work discipline, occupationa safety and heath on the work productivity of employees of PT. JMS Batam by 0.764 or 76.4%. and the remaining 23.6% is explained by other variables outside this research model.